2017
DOI: 10.1257/aer.p20171020
|View full text |Cite
|
Sign up to set email alerts
|

Declining Dynamism, Allocative Efficiency, and the Productivity Slowdown

Abstract: A large literature documents declining measures of business dynamism including high-growth young firm activity and job reallocation. A distinct literature describes a slowdown in the pace of aggregate labor productivity growth. We relate these patterns by studying changes in productivity growth from the late 1990s to the mid 2000s using firm-level data. We find that diminished allocative efficiency gains can account for the productivity slowdown in a manner that interacts with the within-firm productivity grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(92 citation statements)
references
References 4 publications
12
78
1
1
Order By: Relevance
“…Importantly, our evidence abstracts from the confounding effect of declining startup rates since we study responsiveness within firm age groups. Our main results are based on plant-level TFP in high- 46 Decker et al (2017) further show that the positive difference between the weighted and the unweighted means reflects a positive relationship between within-firm productivity growth and initial shares (i.e., larger firms have higher within-firm productivity growth). 47 Alon et al (2017) also use the Dynamic Olley Pakes decomposition method described by Melitz and Polanec (2015) to study the productivity slowdown.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Importantly, our evidence abstracts from the confounding effect of declining startup rates since we study responsiveness within firm age groups. Our main results are based on plant-level TFP in high- 46 Decker et al (2017) further show that the positive difference between the weighted and the unweighted means reflects a positive relationship between within-firm productivity growth and initial shares (i.e., larger firms have higher within-firm productivity growth). 47 Alon et al (2017) also use the Dynamic Olley Pakes decomposition method described by Melitz and Polanec (2015) to study the productivity slowdown.…”
Section: Discussionmentioning
confidence: 57%
“…However, as discussed by Decker et al (2017), the unweighted measure overwhelmingly describes very small firms (more than 90 percent of firms have fewer than 20 45 Importantly, these measures of within-firm productivity growth exploit the RE-LBD's longitudinal links and are therefore distinct from exercises that measure average productivity growth among specific groups of firms. employees).4 5F 46 In sum, within-firm improvements (e.g., innovation by incumbents) have not quickened to compensate for weaker reallocation.4 6F…”
Section: Changing Patterns Of Within-firm Productivity Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent careful review of the evidence (Byrne et al, 2016) demonstrated these points and its summary of the history of TFP growth is reported in Table 1. 1 The mainstream view which is represented by these authors is that slower TFP growth in the recent past reflects a weaker impact from technological progress. It should, however, be noted that an alternative school of thought stresses the role of 'declining business dynamism' (Decker et al, 2017) which entails reduced rates of business start-ups and job reallocation, possible explanations for which might include more onerous regulation or weaker competition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Declining rates of entrepreneurship may be a concern for several reasons. First, as noted above, young firms are important for aggregate job and productivity growth; the decline in entrepreneurship has been associated with a decline in productivity growth (Alon et al 2017;Decker et al 2017b;a) as well as a decline in the job reallocation and labor mar-7 Decker et al (2016) report high annual growth rates among firms at the 90th percentile of the employmentweighted growth rate distribution; these 90th percentile growth rates are such that a 50-employee firm almost doubles in size over one year. The set of firms growing at rates faster than the 90th percentile is much broader than the set of firms that is restricted to the superstar inventors of Akcigit et al (2016) or the set that see the extreme success outcomes of Guzman & Stern (2016), yet these 90th percentile employer businesses are making significant contributions to job growth.…”
Section: Introductionmentioning
confidence: 99%